CRIMINAL JUSTICE SYSTEM IN ERADICATION OF CORRUPTION IN INDONESIA - Bambang Dwi Baskoro; Hartiwiningsih Hartiwiningsih; Hari Purwadi (Fakultas Hukum, Universitas Diponegoro, 2018)
Criminal Justice System in eradication corruption is spesialisation in around General Trial, not yet the same as Usually Criminal Justice System. It’s not integrated like normal criminal justice system, because each other institution work in criminal justice system itself so appearance the fragmentaris and egosectoral.The regulating in Law is criminal justice systemsin eradication corruption emplacedCorruption Eradication Commission ( KPK) as coordinator, supervision, trigger mechanism institution besides as investigators and prosecutor corruption.